2018
DOI: 10.1155/2018/1941728
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection as a Risk Factor for Hepatocellular Carcinoma: A Case-Control Study in Ethiopia

Abstract: Background and Aims. Hepatocellular carcinoma is a major cause of cancer death worldwide, accounting for over half a million deaths per year. Its incidence varies with geographic locations and the type of etiologic factors. In Ethiopia, unidentified causes of liver disease are of sizeable proportion. Recent studies have shown an association of H. pylori infection with different spectrums of chronic liver disease. This study was conducted at St. Paul's Hospital Millennium Medical College in Ethiopia and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Hp has been demonstrated to promote the development of gastric cancer 16,17,18 Recently, it was reported that Hp correlated with increased cancer risk in the digestive system (such as pancreatic cancer and hepatocellular carcinoma). 10,11 The opinions in previous studies are still conflicting regarding Hp with CRA risk. 12,13,19 According to previous studies, Hp infection increases the CRA incidence 12,19 ; however, there is also a study reporting that…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hp has been demonstrated to promote the development of gastric cancer 16,17,18 Recently, it was reported that Hp correlated with increased cancer risk in the digestive system (such as pancreatic cancer and hepatocellular carcinoma). 10,11 The opinions in previous studies are still conflicting regarding Hp with CRA risk. 12,13,19 According to previous studies, Hp infection increases the CRA incidence 12,19 ; however, there is also a study reporting that…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Recently, accumulating evidence revealed that Hp is not only a risk factor for gastric cancer, but also a factor presenting with a carcinogenic effect on other digestive cancers such as hepatobiliary and pancreatic. 10,11 Considering the potential carcinogenic effect of Hp in these digestive cancers, we hypothesized that Hp might also contribute to the development and progression of CRA. However, several studies with small samples drew contradictory results with respect to the association of Hp infection with CRA risk; some studies discovered that Hp infection was associated with higher CRA risk, while some studies reported that there was no association of Hp infection with CRA risk.…”
Section: Introductionmentioning
confidence: 99%
“…A striking study by Isave et al demonstrated the colonization of H. pylori in the hepatobiliary system of cirrhosis patients with a frequency of 50% [14]. Their findings support the studies that were pointed out toward the H. pylori infection and hepatocellular carcinoma [15]. On…”
Section: Discussionmentioning
confidence: 56%
“…A striking study by Isave et al demonstrated the colonization of H. pylori in the hepatobiliary system of cirrhosis patients with a frequency of 50% [14]. Their findings support the studies that were pointed out toward the H. pylori infection and hepatocellular carcinoma [15]. On the other hand, the relationship between H. pylori infection and cardiovascular diseases, chronic metabolic diseases, such as diabetes mellitus, and hyperlipidemia has been argued [16,17].…”
Section: Discussionmentioning
confidence: 61%
“…Mekonnen et al also reported a possible association between H pylori infection and hepatocellular carcinoma (HCC). In particular, 120 Ethiopian patients with HCC were studied, showing a positive correlation with H pylori even after adjustment for potential confounders (OR 5.22; CI 95%: 2.04‐13.31; P < .001) …”
Section: Hepatobiliary and Pancreatic Diseasesmentioning
confidence: 99%